Nose-to-Brain Delivery of Chitosan-Grafted Leciplexes for Promoting the Bioavailability and Antidepressant Efficacy of Mirtazapine: In Vitro Assessment and Animal Studies - Amani M. El Sisi; Essam M. Eissa; Ahmed H. E. Hassan; Marina A. Bekhet; Fatma I. Abo El-Ela; Eun Joo Roh; Rasha M. Kharshoum; Adel A. Ali (Pharmaceuticals)
Background/Objectives: Mirtazapine (MRZ) is a psychotropic drug prescribed to manage serious sorts of depression. By virtue of its extensive initial-pass metabolic process with poor water solubility, the ultimate bioavailability when taken orally is a mere 50%, necessitating repeated administration. The current inquiry intended to fabricate nose-to-brain chitosan-grafted cationic leciplexes of MRZ (CS-MRZ-LPX) to improve its pharmacokinetic weaknesses and boost the pharmacodynamics aspects. Methods: Primarily, MRZ-loaded leciplexes (MRZ-LPXs) were fabricated and tailored employing a central composite design (CCD). Vesicle diameter size (VS), entrapment efficiency (EE %), cumulative MRZ release percentage (CMRZR %), and total quantity penetrating after twenty-four hours (Q24) were the four parameters assessed. Then, the determined optimum formulation was coated with chitosan (CS-MRZ-LPX) and utilized in pharmacodynamics investigations and in vivo biologic distribution studies in Wistar male rats. Results: The customized MRZ-LPX formulation had a diameter size of 186.2 ± 3.5 nm and drug EE of 45.86 ± 0.76%. Also, the tailored MRZ-LPX formulation had a cumulative amount of MRZ released of 76.66 ± 3.06% and the total Q24 permeated was 383.23 ± 13.08 µg/cm2. Intranasal delivery of the tailored CS-MRZ-LPX revealed notably superior pharmacokinetic attributes inside the brain and circulation compared to the orally administered MRZ suspension and the intranasal free drug suspension (p < 0.05); the relative bioavailability was 370.9% and 385.6% for plasma and brain, respectively. Pharmacodynamics’ and immunohistopathological evaluations proved that optimum intranasal CS-MRZ-LPX boosted antidepressant activity compared to the oral and free nasal drug administration. Conclusions: CS-MRZ-LPX tailored formulation can potentially be regarded as a prospective nano platform to boost bioavailability and enhance pharmacodynamics efficacy. Ultimately, intranasal CS-MRZ-LPX can be considered a promising avenue for MRZ targeted brain delivery as an antidepressant.